Impact of elevated carbon dioxide on the protective enzymes in brown planthopper (Nilaparvata lugens) and infested rice (Oryza sativa) plants - DARAVATH, VEERANNA; CHANDER, SUBHASH; SAGAR, D (The Indian Journal of Agricultural Sciences, 2018)
The effect of elevated carbon dioxide (CO2) on protein content, and catalase and peroxidase activity in rice (Oryza sativa L.) plant and brown planthopper (BPH) [Nilaparvata lugens (stal)] was studied in open top chamber (OTC) at elevated CO2 (570Â±25 Î¼l/l) compared to ambient CO2 (400Â±25 Î¼l/l). Uninfested rice plants under elevated CO2 had lower protein content but increased activity of both catalase and peroxidase compared to ambient CO2. The BPH infested rice plants had significantly lower protein content (15.89 g/l) and reduced catalase activity (0.78 Î¼moles of H2O2 decomposed/min/mg of protein) under both elevated and ambient CO2 conditions compared to uninfested rice plant. However, the activity of peroxidase in infested rice plant was non-significantly increased at both elevated and ambient CO2 compared to uninfested rice plants, indicating perhaps that it is an important enzyme in plant defence against BPH in addition to elevated CO2. Further, lower protein content in rice plants under elevated CO2 resulted in lower protein in BPH that fed on them. The activity of catalase and peroxidase in BPH was enhanced when they were fed rice plants under elevated CO2 compared to ambient CO2.